(untitled) (Journal of Patan Academy of Health Sciences, 2020)
This is the experience of medical students during COVID-19 in Shanghai; following the outbreak of corona virus and lockdown of Wuhan, China, on 23 January 2020, one day before the Chinese new year eve.1,2 Since then, the virus has been declared a global pandemic, and life around the world has come to an abrupt halt. On the other hand, things in Wuhan and China have started picking up, following lifting of the 76-Day long lockdown on 7 April.3 The recovery in China, Korea, and Singapore shows promise and hope for the rest of the world, to persevere and weather out the storm. Daily cases in China is in single digit now, and most are imported cases.4 Shanghai reported one imported case of COVID-19, zero locally transmitted case on Thursday 23 April, with a total of 339 locally transmitted confirmed cases, including seven deaths till date, and 1,618 imported cases in mainland China.5,6 No deaths have been reported from the imported cases.6